2006
DOI: 10.1080/13647830500472354
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear cellular instabilities of planar premixed flames: numerical simulations of the Reactive Navier–Stokes equations

Abstract: Abstract. Two-dimensional compressible Reactive Navier-Stokes numerical simulations of intrinsic planar, premixed flame instabilities are performed. The initial growth of a sinusoidally perturbed planar flame is first compared with the predictions of a recent exact linear stability analysis, and it is shown the analysis provides a necessary but not sufficient test problem for validating numerical schemes intended for flame simulations. The long-time nonlinear evolution up to the final nonlinear stationary cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The comparison with the high activation energy asymptotic expressions showed that for low Le the numerical dispersion relation differs from 332 C. Altantzis and others the theoretical expression. The long-time propagation was numerically simulated in domains with heights equal to approximately six and twelve times λ max , the wave length of the linearly most unstable mode, by Kadowaki, Suzuki & Kobayashi (2005), while Yuan, Ju & Law (2005) and Sharpe & Falle (2006) considered narrower domains (one to three λ max and one to two λ max , respectively). Larger domains of up to 10.6λ max were considered in (Yuan, Ju & Law 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The comparison with the high activation energy asymptotic expressions showed that for low Le the numerical dispersion relation differs from 332 C. Altantzis and others the theoretical expression. The long-time propagation was numerically simulated in domains with heights equal to approximately six and twelve times λ max , the wave length of the linearly most unstable mode, by Kadowaki, Suzuki & Kobayashi (2005), while Yuan, Ju & Law (2005) and Sharpe & Falle (2006) considered narrower domains (one to three λ max and one to two λ max , respectively). Larger domains of up to 10.6λ max were considered in (Yuan, Ju & Law 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, calculations of the fully non-linear stages of the evolution, and studies of how these compare and contrast to the fully non-linear one-step model results, would perhaps be a more important next step. Direct numerical simulations using the two-step model, along the lines of the one-step computations in Sharpe and Falle [13], will be presented in a future article.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that a linear analysis only gives information about stability boundaries, onset and initial growth stage of the instability. It is not relevant to the fully developed non-linear cells, which may be of a quite different characteristic wavelength to that predicted by the linear analysis [13].…”
Section: 11mentioning
confidence: 99%
See 1 more Smart Citation
“…However, calculations of the fully nonlinear stages of the evolution, and studies of how these compare and contrast to the fully nonlinear one-step model results, would perhaps be a more important next step. Direct numerical simulations using the two-step model, along the lines of the one-step computations in Sharpe and Falle [10], will be presented in a future article. Indeed, one purpose of the present work is to provide quantitative results against which simulations can be validated.…”
Section: T B Fixedmentioning
confidence: 99%